(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
Nowadays, the tourism industry is seen to be growing, within which cultural tourism plays its own role in generating a country’s income. The practice of tourists travelling to certain locations to experience and learn about cultural differences is known as cultural tourism. When it comes to cultural tourism, the narrative experience is a vital component for tourists to appreciate the main attraction, therefore, making it narrative tourism. In Malaysia, narrative tourism is still underutilised, and there is limited research in this area. Thus, this article discusses how narrative tourism can be explored in two tourist destinations in Malaysia, namely Pulau Pangkor in Perak and Gunung Santubong in Sarawak. The first finding shows that there is no constructive effort to recognise narrative as a tourism resource for Pulau Pangkor, particularly with regard to the story of the hero, Din Ketolok, as well as a few other monuments that are believed to embody their own meaning and event. Meanwhile, the finding on Gunung Santubong shows that it already has a significant narrative of the battle between the Princesses Santubong and Sejinjang, who were ultimately cursed by the King to become mountains. However, its jungle trek to the mountain peak is not a cultural route, which perhaps would be disappointing to tourists who are interested in cultural routes. Nonetheless, with due work and effort, it could become more exploratory and intriguing as a narrative tourism destination. This study shows how stories can transform both locations into suitable destinations for narrative tourism in order to flourish in cultural tourism. To achieve this, narrative tourism requires special attention from the tourism industry authorities. Full text: PDF